Een ladder tegen de windroos. Nederlands tussen Noord- en Zuid-Europa. Contacten, confrontaties en bemiddelaars - van der Heide, Herman; Pos, Arie; Prandoni, Marco; Ross, Dolores (Lage Landen Studies, 2016)
In the meeting between Northern and Southern Europe - usually considered separate worlds - language and literature are important mediators. In this volume Dutch is a starting, arrival and meeting point for essays on linguistic contrasts and literary confrontations between North and South.